2015
DOI: 10.3329/bjb.v44i1.22726
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes of lentil (Lens culinaris Medik.) under phosphorus deficiency stress

Abstract: Phosphorus deficiency in lentil (Lens culinaris Medik.) resulted in the development of abundant long root hairs which were rudimentary in plants fed with phosphorus. Root and stem diameter as well as thickness of leaf reduced under phosphorus deficiency. The cortical zone of the stem and root was found to decrease under phosphorus deficiency. Vascular area became smaller with less number of xylem vessels and smaller size of the cavity due to phosphorus deficiency. The pith area was increased in the stem under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…in stellar and four patches in cortical region were noticed in both the breeding line and wild types. Similar findings are reported by previous researchers [ 72 ]. There was restricted uptake of Na + and Cl - by the thicker epidermis of root along with 3 layers of sclerenchymatous cortex and 8–9 layers of thin wall parenchyma in tolerant breeding line and tolerant wild accession (6–7 layers) when compared to sensitive cultigen (L-4076).…”
Section: Discussionsupporting
confidence: 93%
“…in stellar and four patches in cortical region were noticed in both the breeding line and wild types. Similar findings are reported by previous researchers [ 72 ]. There was restricted uptake of Na + and Cl - by the thicker epidermis of root along with 3 layers of sclerenchymatous cortex and 8–9 layers of thin wall parenchyma in tolerant breeding line and tolerant wild accession (6–7 layers) when compared to sensitive cultigen (L-4076).…”
Section: Discussionsupporting
confidence: 93%
“…The average root diameter in tolerant group was significantly less under low P as compared to sensitive one indicating the importance of more fine roots in P acquisition. Our result is in agreement with reference [63] who also reported lesser root diameter under low P in lentil. It is shown that shallow root system with more basal roots is efficient in P acquisition in soil with less bioavailable P whereas deeper root system contributes to terminal moisture stress condition [64].…”
Section: Interaction Of Low P and Drought On Growth And Root Traits Isupporting
confidence: 94%
“…S1). Under P deficiency, the observed changes in root anatomy of a variety of species include smaller root diameter and stele diameter, fewer and smaller epidermal cells and metaxylem vessels, reduced percentage of stele area, and fewer cortical cells and xylem vessels (Fohse et al, 1991;Fan et al, 2003;Liu et al, 2004;Sarker et al, 2015).…”
mentioning
confidence: 99%